Impact of an informed choice invitation on uptake of screening for diabetes in primary care (DICISION): randomised trial. - Marteau, T; Mann, E; Prevost, A; Vasconcelos, J; Kellar, I; Sanderson, S; Parker, M; Griffin, S; Sutton, S; Kinmonth, A (2010)
OBJECTIVE: To compare the effect of an invitation promoting informed choice for screening with a standard invitation on attendance and motivation to engage in preventive action. DESIGN: Randomised controlled trial. SETTING: Four English general practices. PARTICIPANTS: 1272 people aged 40-69 years, at risk for diabetes, identified from practice registers using a validated risk score and invited to attend for screening. INTERVENTION: Intervention was a previously validated invitation to inform the decision to attend screening, presenting diabetes as a serious potential problem, and providing details of possible costs and benefits of screening and treatment in text and pie charts. This was compared with a brief, standard invitation simply describing diabetes as a serious potential problem. MAIN OUTCOME MEASURES: The primary end point was attendance for screening. The secondary outcome measures were intention to make changes to lifestyle and satisfaction with decisions made among attenders. RESULTS: The primary end point was analysed for all 1272 participants. 55.8% (353/633) of those in the informed choice group attended for screening, compared with 57.6% (368/639) in the standard invitation group (mean difference -1.8%, 95% confidence interval -7.3% to 3.6%; P=0.51). Attendance was lower among the more deprived group (most deprived third 47.5% v least deprived third 64.3%; P<0.001). Interaction between deprivation and effect of invitation type on attendance was not significant. Among attenders, intention to change behaviour was strong and unaffected by invitation type. CONCLUSIONS: Providing information to support choice did not adversely affect attendance for screening for diabetes. Those from more socially deprived groups were, however, less likely to attend, regardless of the type of invitation received. Further attention to invitation content alone is unlikely to achieve equity in uptake of preventive services. TRIAL REGISTRATION: Current Controlled Trials ISRCTN 73125647.